Applying the 2019 EULAR/ACR lupus criteria to patients from an established cohort: a Latin American perspective. Issue 1 (20th January 2020) - Pons-Estel, Guillermo J; Ugarte-Gil, Manuel Francisco; Harvey, Guillermina B; Wojdyla, Daniel; Quintana, Rosana; Saurit, Verónica; Soriano, Enrique R; Bonfa, Eloisa; Massardo, Loreto; Cardiel, Mario; Vila, Luis M; Griffin, Russell; et al.
Abstract : Objective: To evaluate the performance of the 2019 European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) systemic lupus erythematosus (SLE) criteria in terms of earlier patients' classification in comparison to the 1982/1997 ACR or the 2012 Systemic Lupus International Collaborating Clinics (SLICC) criteria. Materials and methods: Patients from a Latin America, multiethnic, multicentre cohort, where SLE was defined using the physicians' diagnosis, were included. To calculate the sensitivity of the 2019 EULAR/ACR criteria, the 1982/1997 ACR criteria were considered the gold standard. Additionally, comparison of the 1982/1997 ACR criteria and the 2012 SLICC criteria with the 2019 EULAR/ACR criteria was performed. Results: The sensitivity of the 2019 EULAR/ACR criteria when compared with the 1982/1997 ACR criteria as the gold standard was 91.3%. This new set of criteria allowed an earlier SLE patient classification in 7.4% (mean 0.67 years) and 0.6% (mean 1.47 years) than the 1982/1997 ACR and the 2012 SLICC criteria, respectively. Patients accruing the 2019 EULAR/ACR earlier than the 1982/1997 ACR criteria were more likely to have high anti-dsDNA titres; those accruing them later were less likely to have mucocutaneous and joint manifestations; this was not observed when comparing them with the 2012 SLICC criteria. Conclusions: The 2019 EULAR/ACR criteria classified earlier only a small proportion of Latin America patients than with the two other criteria sets in real-life clinical practice scenarios. Further studies in different patient populations are needed before these new criteria are adopted worldwide.